Faith and Learning in Action in Ethical Leadership - Roso, Calvin G. (Christian higher education, 2022)
This study addressed how to use service learning (SL) as a means of faith integration (FI) in a doctoral course on ethical leadership. Based on my 20 years of teaching experience in the field of education, my perception has been that graduate students sometimes complete their degree with a greater emphasis on self-actualization than on serving others. One emphasis of the ethical leadership course that was the context for this study was how to respond to ethical dilemmas through considering the viewpoint of others. Two research questions guided the study: First, how can SL and FI be implemented in a course on ethical leadership in education? Second, how can serving others through faith and learning in action influence the understanding of ethical leadership in doctoral candidates? A scholarship of teaching and learning (SoTL) methodology was implemented in this study. This methodological approach aims to promote course improvement by using student assessments, faculty and student reflections, and/or quantitative data to determine the effectiveness of teaching and learning strategies. The intended outcome of SoTL is for others to use the research findings to improve course construction and student learning within their own academic contexts. The findings of this study indicated that implementing SL activities and FI into the course strengthened students’ application of ethical leadership by having them consider the viewpoint of others. Faculty members teaching courses in ethical leadership and other related courses at Christian universities might be well advised to create SL opportunities to help promote faith and learning.